Study protocol for VIdeo assisted thoracoscopic lobectomy versus conventional Open LobEcTomy for lung cancer, a UK multicentre randomised controlled trial with an internal pilot (the VIOLET study). Issue 10 (14th October 2019) - Lim, Eric; Batchelor, Tim; Shackcloth, Michael; Dunning, Joel; McGonigle, Niall; Brush, Tim; Dabner, Lucy; Harris, Rosie; Mckeon, Holly E; Paramasivan, Sangeetha; Elliott, Daisy; Stokes, Elizabeth A; et al.
Abstract : Introduction: Lung cancer is a leading cause of cancer deaths worldwide and surgery remains the main treatment for early stage disease. Prior to the introduction of video-assisted thoracoscopic surgery (VATS), lung resection for cancer was undertaken through an open thoracotomy. To date, the evidence base supporting the different surgical approaches is based on non-randomised studies, small randomised trials and is focused mainly on short-term in-hospital outcomes. Methods and analysis: The VIdeo assisted thoracoscopic lobectomy versus conventional Open LobEcTomy for lung cancer study is a UK multicentre parallel group randomised controlled trial (RCT) with blinding of outcome assessors and participants (to hospital discharge) comparing the effectiveness, cost-effectiveness and acceptability of VATS lobectomy versus open lobectomy for treatment of lung cancer. We will test the hypothesis that VATS lobectomy is superior to open lobectomy with respect to self-reported physical function 5 weeks after randomisation (approximately 1 month after surgery). Secondary outcomes include assessment of efficacy (hospital stay, pain, proportion and time to uptake of chemotherapy), measures of safety (adverse health events), oncological outcomes (proportion of patients upstaged to pathologic N2 (pN2) disease and disease-free survival), overall survival and health related quality of life to 1 year. The QuinteT Recruitment Intervention is integrated into the trial to optimise recruitment. Ethics and dissemination: This trial has been approved by the UK (Dulwich) National Research Ethics Service Committee London. Findings will be written-up as methodology papers for conference presentation, and publication in peer-reviewed journals. Many aspects of the feasibility work will inform surgical RCTs in general and these will be reported at methodology meetings. We will also link with lung cancer clinical studies groups. The patient and public involvement group that works with the Respiratory Biomedical Research Unit at the Brompton Hospital will help identify how we can best publicise the findings. Trial registration number: ISRCTN13472721